Case Studies of Hospitalized Patients Due to Drug Related Complications - Shrestha, Rajeev; Shakya, Sony; Bista, Durga; Shrestha, Rojeena Koju; Khan, Gulam Muhammad; Joshi, Shreena; Rao, B.S. (Kathmandu University Journal of Science, Engineering and Technology, 2006)
A cross-sectional survey was conducted involving five major hospitals in Nepal covering Kathmandu, Bharatpur, and Palpa during the period from 22nd February to 30th May 2003. Pharmacists and doctors collected data from the in-patient files of those admitted due to drug-related complications (DRC) and entered the details in the study-encounter form. The study excluded outpatients and patients experiencing DRCs outside the hospital. Among 15,624 hospital admissions, 63 (0.4%) were attributed to DRCs. Analgesics were responsible for one-fourth of the complications, while hypersensitivity and gastrointestinal (GI) bleeding separately accounted for nearly one-fifth of the complications. Adverse Drug Reactions (ADRs) caused 51 (80.96%) of the complications, followed by overdose (17.46%) and wrong dose (1.58%). A higher incidence of ADRs was due to analgesics (23.82%), followed by antibacterial agents (17.46%), antitubercular agents (15.87%), central nervous system drugs (11.12%), steroids (4.76%), and miscellaneous drugs (7.93%). Analgesics were the main therapeutic category causing DRCs, with hypersensitivity and GI bleeding being the major complications. ADRs were found to be the major cause, with a higher incidence attributable to analgesics and antibacterial agents. The study provided evidence of the incidence of DRCs.